Daya Simpan Bolu Kukus Dengan Penambahan Belimbing Wuluh (Averrhoa bilimbi) dan Jeruk Nipis (Citrus aurantifolia) Sebagai Pengawet Alami - Handayani, Mis Tutik; , Triastuti Rahayu, S.Si, M.Si (2015)
Sponge cake steamed was one of the traditional cake that favored by people because of the shape and color attractive. The shelf life of sponge cake steamed only 2-3 days. To extend the shelf life, it can be added with material containing flavonoids and phenols, these compounds can be found in starfruit and lime. The purpose of this research was to know shelf life and organoleptic quality of sponge cake steamed with the addition of starfruit and lime. This research used a completely randomized design of two factors: the first factor: type of natural preservative that are P1: starfruit, P2: lime and the second factor was a natural preservative concentration K0: 0%, K1: 2%, K2: 4%, K3: 6%, K4: 8. Research results have shown that shelf life of sponge cake steamed with the addition of starfruit only until day 2 but the number of bacteria at a concentration of 2 % and 4 % more less than addition lime, the shelf life of sponge cake steamed with the addition of lime until day 3. The addition of starfruit and lime was affected the flavor of spone cake steamed, but does not affected the texture of sponge cake steamed.